2021
DOI: 10.1111/hir.12414
|View full text |Cite
|
Sign up to set email alerts
|

Literature searching methods or guidance and their application to public health topics: A narrative review

Abstract: Background: Information specialists conducting searches for systematic reviews need to consider key questions around which and how many sources to search. This is particularly important for public health topics where evidence may be found in diverse sources. Objectives:The objective of this review is to give an overview of recent studies on information retrieval guidance and methods that could be applied to public health evidence and used to guide future searches. Methods: A literature search was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…We included SRs in public health that met the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) definition of a systematic review, that is, articles that explicitly state the methods of study identification (i.e., a search strategy), study selection (e.g., eligibility criteria and selection process), and synthesis (or other types of summary) ( 17 ). Public health is defined as the promotion and protection health and wellbeing, prevention of illness and prolongation of life through organized societal efforts, and it includes three key domains: health improvement, improving services, and health protection ( 18 ). We included only published SRs written in English.…”
Section: Methodsmentioning
confidence: 99%
“…We included SRs in public health that met the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) definition of a systematic review, that is, articles that explicitly state the methods of study identification (i.e., a search strategy), study selection (e.g., eligibility criteria and selection process), and synthesis (or other types of summary) ( 17 ). Public health is defined as the promotion and protection health and wellbeing, prevention of illness and prolongation of life through organized societal efforts, and it includes three key domains: health improvement, improving services, and health protection ( 18 ). We included only published SRs written in English.…”
Section: Methodsmentioning
confidence: 99%
“…35 A literature review by the authors of the current paper identified a lack of research into approaches to public health searching, suggesting that further work modelling different scenarios was needed. 8 This study takes up the challenge and shows the contribution of the sources that were used and then provides scenarios modelling whether a more efficient selection could have been used in a sample of NICE PHGs.…”
Section: Modelling Efficient Searchesmentioning
confidence: 99%
“…The NICE manual warns against retrieving an unmanageable volume of results, even though it requires adequate coverage of the best available evidence 1 . (sec5.1) This can be particularly challenging in public health topics that are difficult to define at the outset, require a range of terminology and must draw on multi‐disciplinary sources 8 . Similarly, authors of social, behavioural, and educational science reviews for the Campbell Collaboration are advised that searches must be ‘thorough’ and ‘identify as many relevant studies as possible’ while being done ‘within resource limits’ 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue takes the broad theme of public health as its inspiration, starting with Heath et al’s (2022) narrative review of literature searching in relation to public health topics, a sector where evidence can be in a diverse set of resources. Analysis of 72 papers provides insight into sources and search techniques.…”
Section: In This Issue…mentioning
confidence: 99%